Aspectos neuropsicológicos asociados a la presencia de síntomas depresivos en niños escolarizados (2012)
ABSTRACT: The purpose of this study was to estimate the presence of depressive symptoms in a nonclinical sample of school children and describe the neuropsychological functioning of children with depressive symptoms to compare them with a similar demographic group without depressive symptoms. To this end the Child Depression Inventory (Children Depression Inventory, CDI) was administered to 312 school children aged between 9 and 12. Based on the results 62 children were selected and distributed into two groups: one with depressive symptoms and one without symptoms. Neuropsychological assessment included: the Perceptions and Differences Test –FACES, the Cancelación de la A [A Cancellation Test], the Trail Making Test (TMT) forms A and B, the Rey Figure Test, the Stroop Test and the California Verbal Learning Test for Children (CVLT). The CDI showed that 13.78% of children have symptoms of depression. Neuropsychological assessment showed only significant differences in the conflict task of the Stroop Test. This suggests that the ability to inhibit automatic responses is affected at a subclinical level.